2023
DOI: 10.1111/ene.15666
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone and custom‐made software to assess the effect of botulinum toxin in essential blepharospasm: Initial results

Abstract: Background and purpose: It is challenging to assess essential blepharospasm (EB) patients objectively because they exhibit chaotic patterns of abnormal eyelid movements.Previously employed objective approaches used systems with low levels of accuracy systems or were too complex to be applied in routine clinical practice. We aimed to develop a practical tool using a smartphone camera and custom-made software to objectively assess the therapeutic effects of botulinum toxin in blepharospasm patients.Methods: Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…4 A practical tool using a smartphone and custom-made software to assess eyelid spasms in these patients has been recently reported and permits the assessment of the response to botulinum toxin injections in clinical practice with higher accuracy than human-based video review analysis. 5 Association between EB and dry eye disease is well known. 1,[6][7][8] However, the effect of BTX-A injections on the ocular surface remains controversial: while some studies reported improvement, some reported worsening or no change in tear film parameters after BTX-A applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 A practical tool using a smartphone and custom-made software to assess eyelid spasms in these patients has been recently reported and permits the assessment of the response to botulinum toxin injections in clinical practice with higher accuracy than human-based video review analysis. 5 Association between EB and dry eye disease is well known. 1,[6][7][8] However, the effect of BTX-A injections on the ocular surface remains controversial: while some studies reported improvement, some reported worsening or no change in tear film parameters after BTX-A applications.…”
mentioning
confidence: 99%
“…4 A practical tool using a smartphone and custom-made software to assess eyelid spasms in these patients has been recently reported and permits the assessment of the response to botulinum toxin injections in clinical practice with higher accuracy than human-based video review analysis. 5…”
mentioning
confidence: 99%